Analisis Kesenjangan Kinerja Aparatur Sipil Negara (ASN) di Pemerintah Kabupaten Sleman - Musyafa'ah, Musyafa'ah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The ASN Performance Assessment aims to ensure the objectivity of civil servant development which is based on an achievement system and career system. Assessment of civil servant work performance is carried out based on objective, measurable, accountable, participatory and transparent principles. ASN work performance assessment consists of two elements, namely, employee work targets (SKP) and employee work behavior. In accordance with Government Regulation Number 30 of 2019 concerning Civil Servant Job Performance Evaluation. In accordance with these regulations. ASN is required to measure performance through a performance measurement system. Performance measurement is carried out on SKP by comparing SKP Realization with SKP Targets and Work Behavior by conducting work behavior assessments. The type of research in this research is qualitative research, the research location is the Sleman Regency Government. The informants consist of the Head of Employee Development and Welfare, BKPP Sleman Regency Head of Subdivision for Administration of National Unity and Political Agencies Head of Subdivision for Administration of UPT Community Health Center 4 Ngemplak I Head of Subdivision for Administration at RSUD Sleman Head of Subdivision for Administration for Environmental Services Head of General Subdivision Kapanewon Head of the General Subdivision of the Health Service, Head of the General Subdivision of the Community Health Center, Paste I. Employees who have a performance gap of 11 people. The technique for determining informants used is a purposive technique. Data collection techniques use observation, documentation and interviews. The data analysis technique is carried out in stages: data identification, data reduction, data presentation, data interpretation and drawing conclusions. The results of the research show that there is a gap in the performance of ASN in the Sleman Regency Government. With the change in paradigm, developing ASN competencies has become a means and capital to obtain relevant competencies so that they can compete and compete in this era of globalization and digital. Ideally, competency development is correlated with increased organizational performance and the direction of national development. By emphasizing competency development using non-classical methods, it can help ASN to obtain their rights, namely that every year they receive at least 20 hours of learning development. Increasing the performance of ASN in the Sleman Regency Government. It is hoped that the use of this digitalization system in the implementation of ASN assessments can reduce fraud and intervention from other parties.